Genetic variant of Interleukin-18 gene is associated with the Frailty Index in the English Longitudinal Study of Ageing - Mekli, Krisztina (Age Ageing, 2015)
Background: the term frailty refers to a condition of increased vulnerability to stressors among older people, leading to a decline in homeostatic reserve. Frailty often leads to falls, hospitalisation and mortality, hence its importance for the delivery of health care to older adults. The pathophysiological mechanisms behind frailty are not well understood, but the decreased steroid-hormone production and elevated chronic systemic inflammation of older people appear to be major contributors. Method: we used a sample of 3,160 individuals aged 50 or older from the English Longitudinal Study of Ageing and assessed their frailty status according to a Frailty Index. We selected 620 single nucleotide polymorphisms in genes involved in the steroid hormone or inflammatory pathways. We performed linear association analysis. The outcome variable was the square root transformation of the Frailty Index, with age and sex entered as covariates. Results: the strongest signal was detected in the pro-inflammatory Interleukin-18 gene (rs360722, P = 0.0021, β = −0.015). Further significant signals were observed in the Interleukin-12 (rs4679868, P = 0.0062, β = −0.008 and rs9852519, P = 0.0077, β = −0.008), low density lipoprotein receptor-related protein 1 (rs1799986, P = 0.0065, β = 0.011) and Selectin-P (rs6131, P = 0.0097, β = −0.01) genes. None of these associations remain significant after Bonferroni correction. Conclusions: we show potential associations between genetic variants of four genes and the frailty index. These genes are involved in the cholesterol transport and inflammatory pathway and, as such, our results provide further support for the involvement of the immunological processes in frailty of the elderly.